Manganese-containing polydopamine nanoparticles as theranostic agents for magnetic resonance imaging and photothermal/chemodynamic combined ferroptosis therapy treating gastric cancer - Zhian Chen; Zhenhao Li; Chuangji Li; Huilin Huang; Yingxin Ren; Zhenyuan Li; Yanfeng Hu; Weihong Guo (Drug Delivery, 2022)
Gastric cancer (GC) is a serious disease with high morbidity and mortality rates worldwide. Chemotherapy plays a key role in GC treatment, while inevitable drug resistance and systematic side effects hinder its clinical application. Fenton chemistry-based chemodynamic therapy (CDT) has been used as a strategy for cancer ferroptosis, and the CDT efficiency could be enhanced by photothermal therapy (PTT). With the trend of treatment and diagnosis integration, the combination of magnetic resonance imaging (MRI) and CDT/PTT exhibits enormous progress. Herein, we constructed a platform based on PEGylated manganese-containing polydopamine (PDA) nanoparticles, named as PEG-PDA@Mn (PP@Mn) NPs. The PP@Mn NPs were stable and globular. Furthermore, they demonstrated near-infrared (NIR)-triggered PTT and Fenton-like reaction-based CDT effects and T1-weighted MRI capabilities. According to in vitro studies, the PP@Mn NPs trigger ferroptosis in cancer cells by producing abundant reactive oxygen species (ROS) via a Fenton-like reaction combined with PTT. Furthermore, in vivo studies showed that, under MRI guidance, the PP@Mn NPs combined with the PTT at the tumor region, have CDT anti-tumor effect. In conclusion, the PP@Mn NPs could provide an effective strategy for CDT/PTT synergistic ferroptosis therapy for GC.